2022
DOI: 10.3390/separations9040091
|View full text |Cite
|
Sign up to set email alerts
|

QuEChERS Method Combined with Gas- and Liquid-Chromatography High Resolution Mass Spectrometry to Screen and Confirm 237 Pesticides and Metabolites in Cottonseed Hull

Abstract: Cottonseed hull is a livestock feed with large daily consumption. If pesticide residues exceed the standard, it is easy for them to be introduced into the human body through the food chain, with potential harm to consumer health. A method for multi-residue analysis of 237 pesticides and their metabolites in cottonseed hull was developed by gas-chromatography and liquid-chromatography time-of-flight mass spectrometry (GC-QTOF/MS and LC-QTOF/MS). After being hydrated, a sample was extracted with 1% acetic acid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Contrary to previous data, our study did not unambiguously detect some FAs (oleic acid, stearic acid and α-linolenic acid) usually found in soybeans. These results confirm the influence of the germplasm on the fatty acid content of the seeds, which has been explained by the duration of seed filling, including the time to maturity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In 2019, Seym et al found the highest concentrations of linoleic acid (C18:2) in industrially processed soybean oils, compared to myristic acid (C14:0), palmitic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1), and linolenic acid (C18:3) [ 25 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Contrary to previous data, our study did not unambiguously detect some FAs (oleic acid, stearic acid and α-linolenic acid) usually found in soybeans. These results confirm the influence of the germplasm on the fatty acid content of the seeds, which has been explained by the duration of seed filling, including the time to maturity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In 2019, Seym et al found the highest concentrations of linoleic acid (C18:2) in industrially processed soybean oils, compared to myristic acid (C14:0), palmitic acid (C16:0), palmitoleic acid (C16:1), stearic acid (C18:0), oleic acid (C18:1), and linolenic acid (C18:3) [ 25 ].…”
Section: Discussionsupporting
confidence: 80%
“…Nowadays, the “quick, easy, cheap, effective, rugged, and safe” (QuEChERS) method is an accepted analysis and extraction of pesticides in plant materials [ 16 ], especially in different plant extracts, such as vegetables containing high amounts of oils [ 15 ]. In 2022, Tong et al combined the advantages of QuEChERS and gas and liquid chromatography high-resolution mass spectrometry to analyze fatty acid compositions and levels of pesticide residues [ 17 ]. It was confirmed that such a combination of analysis methods is suitable for the pesticide multiresidue determination of soybean-based beverages in routine laboratory analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The other three manuscripts focus on multi-pesticide analysis via HRMS. Chen and coworkers coupled the QuEChERS method with time-of-flight mass spectrometry for hundreds of pesticides in cottonseed hull [12] and raw milk samples [13]. For the oily samples, acetonitrile with 1% acetic acid was selected as an extraction solvent, followed by purification with MgSO 4 , C 18 , or primary secondary amine sorbents.…”
Section: Summary Of Published Articlesmentioning
confidence: 99%